Implikasi PPAT sebagai Pejabat Umum dalam Kasus Sertifikat Ganda pada Pengumpulan Data Sporadik - Mubarok, Muhammad Irham Husni; Nurlaela, Indah (Jurnal Syariah dan Hukum Komparatif, 2025)
Duplicate land certificates are a recurring issue in land management in Indonesia and have the potential to trigger serious agrarian conflicts. The Land Deed Making Official (PPAT) plays a critical role in data collection and certificate verification, particularly in the process of drafting deeds for sale and purchase, grants, or other transfers of land rights. However, in several cases, negligence or lack of due diligence by the PPAT during sporadic data collection has led to the issuance of duplicate land certificates. This article examines the legal implications, responsibilities, and preventive measures that must be undertaken by PPATs in addressing duplicate certificate cases, especially those arising from sporadic data collection. Research findings indicate that the primary cause of duplicate certificates is inaccurate data during the sporadic data collection process, compounded by weak oversight and verification by the PPAT. A PPAT may be held legally accountable if proven negligent in the execution of their duties. The legal consequences for a PPAT may include administrative sanctions, liability for damages, and, in certain cases, criminal penalties. Therefore, improving the accuracy and transparency of data collection, along with strict law enforcement, is essential to prevent the recurrence of duplicate land certificate cases in the future.